New Bangalores? The role of Central and Eastern Europe in business and IT services offshoring - Gal, Zoltan (Journal of Economic Development, Environment and People, 2013)
The paper discusses how the second global shift in business services provision and corporate restructuring open up new offshoring opportunities into Central and Eastern Europe (CEE). It explores three issues: First, it builds upon the theoretical framework of the ‘new paradigm of globalization, which considers offshoring as one of the most important globalizing forces of recent time. This results in a shift in global trade, namely from ‘trade in goods’ to ‘trade in tasks’ determined by the changing trends in the division of labour. Second, the paper gives an overview of services relocation into CEE in comparison with its Asian counterparts. As the EU expanded eastwards, the opportunities for European corporations to offshore their business services to these ‘nearshore’ locations increased. Building on the region’s nearshoring advantages such as geographical-cultural proximity and on their multilingual graduate sup ply, CEE is likely to utilise more value added quality-driven BPO and KPO services. Third, the paper examines the implications of offshoring for the home markets in CEE assessing its impact on their locations. It reveals the role of offshoring activities in the metropolitan transformation and discusses the factors that make the capital cities an increasingly attractive option for companies to relocate their services. Despite CEE has taken advantage on the trend supported by the global service delivery models reducing dependency on any single location, its further growth may be influenced by the worsening macro-conditions, and future prospect of the region depends largely on government incentives and on the success of exploiting talent pools offered by its provincial cities.